(untitled) (Annals of Medical Research, 2021)
Aim: Lung transplantation is the only therapeutic option that can improve survival and quality of life for idiopathic pulmonary fibrosis (IPF) despite recent advances in medical treatment. This study aimed to analyze mortality during the waiting list in IPF patients listed for lung transplantation since the implementation of the lung transplant program.Materials and Methods: Patients with IPF listed for lung transplantation were retrospectively analyzed between December 2016 and December 2018. Moreover, patients were excluded if they have been referred for lung transplantation and were not suitable after evaluation.Results: A total of 28 patients with IPF were listed for lung transplantation. The waiting list mortality rate was 39.3% (11/28). The median days on the waiting list were 71.2 days (range, 3–206) in patients who underwent lung transplantation and 110 days (range, 14–303) in patients who died on the waiting list. No differences in the demographic and clinical data were observed between both groups. Arterial blood gas saturation was statistically significantly lower in patients who died on the waiting list (74.2% vs. 82.9%, p = 0.046). Two single and 15 bilateral lung transplants were performed. Hospital mortality rate was 23.5% (4/17). The 1- and 3-year survival rates were 70.6%.Conclusion: Lung transplantation is the only treatment option for patients with IPF who are not responsive to medicinal treatment. The late referral may lead to mortality on the waiting list. Thus, patients newly diagnosed with IPF should be promptly referred to a transplant center for evaluation.